Laboratory Patterns in Hypoglycin A Toxicity - Pitkin, Fabian; Randall, Sala (Archives of Clinical and Biomedical Research, 2017)
The unripe fruit of the ackee tree (Blighia Sapida), contains significantly high concentrations of the hypoglycin (L-α - amino-β -[methylene cyclopropyl] propionic acid) a toxin implicated in over 5000 deaths worldwide. Methylenecyclopropane acetyl CoA (MCPA-CoA) a metabolite of hypoglycin A, inhibits several coenzyme A dehydrogenases which are essential for gluconeogenesis resulting in depletion of glucose reserves and the inability of cells to regenerate glucose; eventually leading to hypoglycaemia. This study aimed at reviewing literature on the hypoglycin A toxicity, add to the body of tests already established by the WHO in detecting hypoglycin toxicity based on the patterns we have observed and to provide physicians with a simple panel of tests that will aid in the speedy detection of hypoglycin A toxicity for more timing therapeutic intervention. This review covers the description, pathophysiology, epidemiology, and clinical presentation. In addition, data on patients diagnosed with hypoglycin A toxicity was collected and analysed for significant trends. Analysis of data determined that 86%, 97% and 79% of patients demonstrated significant increase in phosphorous (95% CI of 1.74-2.73), anion gap (95% CI 24.26-29.05) and AST (95% CI 37.97-73.06) respectively. On the other hand, 95%, and 92% of patients demonstrated significant decrease in bicarbonate (95% CI of 13.02-16.56) and Lymphocytes count 95% CI of 7.49-12.81 respectively. Significantly low random plasma glucose levels, in conjunction with elevated levels of Phosphorus, Anion gap, and AST, as well as decreased levels of bicarbonate, and an absolute lymphocyte count could prove an effective screening for Hypoglcyin A toxicity in affected regions.